Synthesis method of 4-fluoro-2-methoxy-5-nitroaniline
By modifying the Rainey nickel catalyst and a specific nitration system, the problems of low reaction yield and high catalyst brittleness in the synthesis method of 4-fluoro-2-methoxy-5-nitroaniline in the prior art are solved, and the effects of high purity, high yield and long-life catalysts are achieved.
Patent Information
- Application Number
- CN202510018985.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
In the synthesis method of 4-fluoro-2-methoxy-5-nitroaniline in the prior art, the nitration reaction conditions are not completely screened, resulting in a low reaction yield, and the Rainey nickel catalyst is highly brittle, prone to fracture, cracking and failure, and the catalytic activity is reduced.
The modified Rainey nickel catalyst is used to improve the purity and yield of 4-fluoro-2-methoxy-5-nitroaniline through specific nitration systems and nitrifying agent addition, and a highly active catalyst is formed through corona treatment and cold plasma treatment.
The purity and yield of 4-fluoro-2-methoxy-5-nitroaniline are improved, the service life of the catalyst is extended, the production cost is reduced, and the self-cleaning function of the catalyst is enhanced.
Smart Images

Figure BDA0005230746120000051 
Figure BDA0005230746120000052 
Figure BDA0005230746120000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic synthesis, and specifically relates to a method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline. Background Art
[0002] 4-Fluoro-2-methoxy-5-nitroaniline, as an important intermediate of anticancer drugs, can participate in the synthesis and preparation of osimertinib. The reported method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline is to prepare it by nitration of 4-fluoro-2-methoxyaniline, but in this step, the conditions affecting the nitration reaction are not fully screened, resulting in a low reaction yield; in addition, for the reduction reaction of the nitro group, the most commonly used is the Raney nickel hydrogenation system.
[0003] Raney nickel is a solid catalyst with a porous structure and a large specific surface area. Its main components are nickel and a small amount of aluminum. It can be used for the addition reaction of unsaturated compounds such as olefins, alkynes, nitrogen-nitrogen double bonds, nitriles, dienes, aromatic hydrocarbons, etc. with hydrogen. The catalytic activity of Raney nickel comes from the catalytic properties and porous structure of nickel itself, and the effect of the leaching reaction will directly affect the microscopic morphology of the porous structure, thereby affecting the catalytic activity. During the leaching reaction, if the corrosion and dissolution rate of the aluminum component is too slow, the generated aluminum hydroxide will not have time to be further converted into sodium aluminate and will block the generated pores, thereby preventing sodium hydroxide from entering the alloy to further corrode aluminum, resulting in a decrease in catalytic activity. If the corrosion and dissolution rate of the aluminum component is too fast, it is easy to cause the pore wall to collapse and adhere, which also affects the leaching effect. Therefore, improving the catalytic activity is a technical problem that technicians need to solve urgently. Moreover, the Raney nickel catalyst on the market today is very brittle and prone to fracture and cracking failure. It is very easy to burn when exposed to the air, which is dangerous.
[0004] Based on this, we proposed a method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline, hoping to solve the shortcomings of the prior art. Summary of the invention
[0005] The purpose of the present invention is to provide a method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline in view of the existing problems.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline comprises the following steps:
[0008] S1, methanol, 5-fluoro-2-nitroanisole, and modified Raney nickel catalyst are added to a hydrogenation kettle in sequence, hydrogen is introduced and the air is replaced three times, and the reaction is carried out under normal temperature and pressure conditions with stirring. After the reaction is completed, the modified Raney nickel catalyst is filtered out, and then rinsed with methanol, the filtrate is collected and concentrated to obtain 4-fluoro-2-methoxy-5-nitroaniline intermediate I;
[0009] S2. Add sulfuric acid to the reaction kettle, cool to 10-20°C, add 4-fluoro-2-methoxy-5-nitroaniline intermediate I dropwise while stirring, after the addition is completed, continue stirring for 1-2 hours, cool the reaction system to 6°C, then add potassium nitrate-cerium nitrate mixture in batches while performing gradient cooling, react in an ice bath at 0°C for 3-4 hours, adjust the system pH to 9-10 with liquid alkali, centrifuge and filter, wash the filter cake with water to obtain 4-fluoro-2-methoxy-5-nitroaniline wet product I filter cake, return the filter cake to the kettle, add water to pulp at room temperature, centrifuge, continue to wash the filter cake with water to obtain 4-fluoro-2-methoxy-5-nitroaniline wet product II filter cake, return the filter cake to the kettle, add ethanol to heat and dissolve, cool to -5-5°C, keep warm for crystallization, centrifuge, rinse with ethanol, and vacuum dry to obtain 4-fluoro-2-methoxy-5-nitroaniline.
[0010] Preferably, the preparation of the modified Raney nickel catalyst comprises the following steps:
[0011] (1) high-purity nickel and aluminum are smelted in a furnace, and after they are completely melted, lanthanum chloride is added to continue smelting, and after quenching and cooling, they are added to a ball mill for ball milling to obtain alloy powder for use;
[0012] (2) grinding the chitosan nanofibers and the alloy powder in a bead mill at a weight ratio of 1:1 to 4, grinding at 2000 to 3000 rpm for 10 to 16 minutes, and then placing the mixture in a corona machine for corona treatment. After the grinding, a mixed powder I is obtained for use.
[0013] (3) Ultrasonic dispersion of the mixed powder I in a sodium hydroxide solution, stirring at 60-80°C and 300-500 rpm for 4-6 hours, adding anhydrous ethanol solution of salicylic acid, stirring and refluxing at 60-80°C and 300-500 rpm for 4-6 hours, filtering, washing with anhydrous ethanol 3-5 times, drying in a vacuum drying oven at 40-50°C to constant weight, adding anhydrous methanol solution of sodium borohydride, filtering after sufficient reaction, washing with deionized water 3-5 times, drying in a vacuum drying oven at 40-50°C to constant weight, adding anhydrous ethanol solution of iodomethane, sodium hydroxide and sodium iodide, reacting at 60-70°C for 10-12 hours, filtering, washing with anhydrous ethanol 2-3 times, washing with deionized water 3-6 times, and finally placing
[0014] Dry in a vacuum drying oven at 40-50°C to constant weight to obtain mixed powder II;
[0015] (4) The mixed powder II obtained in step (3) is placed in a DBD cold plasma device for cold plasma treatment and taken out after completion.
[0016] Preferably, the mass ratio of nickel to aluminum in step (1) is 1:0.7-0.9, and the mass of lanthanum chloride is 8-10% of the total mass of nickel and aluminum;
[0017] The grinding speed of the ball mill is 300-400 rpm.
[0018] Preferably, the voltage of the corona treatment in step (2) is 5 to 10 kV / m 2 The corona treatment time is 10 to 12 minutes.
[0019] Preferably, the weight volume ratio of the mixed powder I described in step (3) to the sodium hydroxide solution is 1 g: 4-5 mL;
[0020] The weight-volume ratio of the mixed powder I to the anhydrous ethanol solution of salicylic acid is 1 g: 3-4 mL;
[0021] The volume ratio of the anhydrous ethanol solution of salicylic acid, the anhydrous methanol solution of sodium borohydride and the anhydrous ethanol solution of methyl iodide, sodium hydroxide and sodium iodide is 1:1:2-3.
[0022] Preferably, the power of the cold plasma treatment in step (4) is 1 to 3 kW, and the number of treatments is 3 to 9 times.
[0023] Preferably, the weight ratio of 5-fluoro-2-nitroanisole to the modified Raney nickel catalyst in step S1 is 10 to 20:1;
[0024] The weight volume ratio of the 5-fluoro-2-nitroanisole and methanol is 1 g:8-10 mL.
[0025] Preferably, the weight ratio of the 4-fluoro-2-methoxy-5-nitroaniline intermediate I and potassium nitrate in step S2 is 1:0.7-0.8;
[0026] The concentrated sulfuric acid is 98% sulfuric acid by mass;
[0027] The weight-to-volume ratio of the 4-fluoro-2-methoxy-5-nitroaniline intermediate I and concentrated sulfuric acid is 1 g:1-2 mL.
[0028] Preferably, the specific operation of adding the potassium nitrate-cerium nitrate mixture in batches while the gradient cooling described in step S2 is: adding the potassium nitrate-cerium nitrate mixture once every 6 to 8 minutes, maintaining the system temperature at 8 to 10°C when the potassium nitrate-cerium nitrate mixture is added for the first time, and reducing the system temperature by 1 to 2°C each time the potassium nitrate-cerium nitrate mixture is added until it drops to 0°C, and the potassium nitrate-cerium nitrate mixture added each time is equal.
[0029] Preferably, the potassium nitrate-cerium nitrate mixture is prepared by adding potassium nitrate and cerium nitrate into deionized water at a mass ratio of 1:0.1 to 0.16, dissolving the mixture, mixing the mixture, and then drying the mixture.
[0030] The reaction process of step S1 is as follows:
[0031]
[0032] The reaction process of step S2 is as follows:
[0033]
[0034] Compared with the prior art, the present invention has the following advantages:
[0035] When synthesizing 4-fluoro-2-methoxy-5-nitroaniline, the invention uses 5-fluoro-2-nitroanisole as a raw material, uses specially prepared modified Raney nickel as a catalyst for hydrogenation reduction, synthesizes 4-fluoro-2-methoxyaniline, and then uses a special nitration system and adjusts the adding mode of the nitrating agent to promote the formation of the target product, thereby improving the purity and yield of the product 4-fluoro-2-methoxy-5-nitroaniline.
[0036] Specifically, high-purity nickel, aluminum and lanthanum chloride are melted in a furnace to obtain alloy powder, chitin nanofibers and alloy powder are ground and mixed, the grinding speed is controlled, the shear force generated by grinding causes part of the molecular chains in the chitin nanofibers to break, and chitin salts with positive charges are generated. Nanofibers formed by these chitin salts with positive charges are enriched on the surface of the alloy powder, and free radicals are also generated at the same time. At this time, corona treatment is performed, and corona discharge generates plasma on the surface of the mixed powder. Ions and free radicals in the plasma react with molecules on the surface of the powder to generate polar groups, and then quaternary ammonium salt groups are introduced by activation, and quaternization treatment is performed. Finally, cold plasma treatment is performed, and the active free radicals generated on the surface are used to trigger functional monomers to carry out graft copolymerization on the material surface to form a stable and highly active catalyst with a hierarchical aperture structure. The catalyst has high catalytic stability in the reaction system of the present invention, can maintain its active selectivity during multiple uses and for a long time, and has a long service life. The catalyst also has a self-cleaning function, can remove impurities through ion exchange, and play a catalytic role in chemical reactions, further improving the catalytic performance. During the reaction, it can automatically remove impurities deposited on the surface and maintain its catalytic activity, thereby extending the service life of the catalyst and improving the catalytic efficiency. The catalyst can be recycled for a long time and does not need to be replaced frequently, thereby reducing production costs, reducing the generation of waste, and achieving higher yields and higher product quality. DETAILED DESCRIPTION
[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0038] Preparation Example 1
[0039] The preparation of modified Raney nickel catalyst comprises the following steps:
[0040] (1) high-purity nickel and aluminum are smelted in a furnace at a mass ratio of 1:0.7, and after they are completely melted, lanthanum chloride of 8% of the total mass of nickel and aluminum is added to continue smelting, and after quenching and cooling, the mixture is added to a ball mill at 300 rpm to obtain alloy powder for later use;
[0041] (2) The chitosan nanofibers and alloy powder were placed in a bead mill at a weight ratio of 1:1 for grinding. After grinding at 2000 rpm for 10 min, they were placed in a corona machine for corona treatment at a voltage of 5 kV / m 2 , after corona treatment for 10 minutes, the mixed powder I is ready for use;
[0042] (3) The mixed powder I is ultrasonically dispersed in a sodium hydroxide solution and stirred at 60°C and 300 rpm for 4 h. Then, an anhydrous ethanol solution of salicylic acid is added, and the mixture is stirred and refluxed at 60°C and 300 rpm for 4 h. The mixture is filtered, washed with anhydrous ethanol for 3 times, dried in a vacuum drying oven at 40°C to constant weight, and then an anhydrous methanol solution of sodium borohydride is added. After sufficient reaction, the mixture is filtered, washed with deionized water for 3 times, dried in a vacuum drying oven at 40°C to constant weight, and then an anhydrous ethanol solution of iodomethane, sodium hydroxide, and sodium iodide is added. The mixture is reacted at 60°C for 10 h, filtered, washed with anhydrous ethanol for 2 times, washed with deionized water for 3 times, and finally dried in a vacuum drying oven at 40°C to constant weight to obtain a mixed powder II.
[0043] (4) The mixed powder II obtained in step (3) is placed in a DBD cold plasma device at 1 kW, treated three times, and then taken out to obtain a modified Raney nickel catalyst I.
[0044] The weight volume ratio of the mixed powder I described in step (3) to the sodium hydroxide solution is 1 g:4 mL;
[0045] The weight-to-volume ratio of the mixed powder I to the anhydrous ethanol solution of salicylic acid is 1 g:3 mL;
[0046] The volume ratio of the anhydrous ethanol solution of salicylic acid, the anhydrous methanol solution of sodium borohydride, and the anhydrous ethanol solution of methyl iodide, sodium hydroxide, and sodium iodide is 1:1:2.
[0047] Preparation Example 2
[0048] The preparation of modified Raney nickel catalyst comprises the following steps:
[0049] (1) high-purity nickel and aluminum are smelted in a furnace at a mass ratio of 1:0.8, and after they are completely melted, lanthanum chloride is added at 9% of the total mass of the nickel and aluminum and the smelting is continued. After quenching and cooling, the mixture is added to a ball mill at 350 rpm to obtain alloy powder for later use;
[0050] (2) The chitosan nanofibers and alloy powder were placed in a bead mill at a weight ratio of 1:2.5 for grinding. After grinding at 2500 rpm for 13 min, they were placed in a corona machine for corona treatment at a voltage of 8 kV / m 2 , after corona treatment for 11 minutes, the mixed powder Ⅰ is ready for use;
[0051] (3) The mixed powder I is ultrasonically dispersed in a sodium hydroxide solution and stirred at 70°C and 400 rpm for 5 h. Then, an anhydrous ethanol solution of salicylic acid is added, and the mixture is stirred and refluxed at 70°C and 400 rpm for 5 h. The mixture is filtered, washed with anhydrous ethanol for 4 times, dried in a vacuum drying oven at 45°C to constant weight, and then an anhydrous methanol solution of sodium borohydride is added. After sufficient reaction, the mixture is filtered, washed with deionized water for 4 times, dried in a vacuum drying oven at 45°C to constant weight, and then an anhydrous ethanol solution of iodomethane, sodium hydroxide, and sodium iodide is added. The mixture is reacted at 65°C for 11 h, filtered, washed with anhydrous ethanol for 2 times, washed with deionized water for 4 times, and finally dried in a vacuum drying oven at 45°C to constant weight to obtain a mixed powder II.
[0052] (4) The mixed powder II obtained in step (3) is placed in a DBD cold plasma device at 2 kW, and after being treated 6 times, it is taken out to obtain a modified Raney nickel catalyst II.
[0053] The weight volume ratio of the mixed powder I described in step (3) to the sodium hydroxide solution is 1 g:4.5 mL;
[0054] The weight-volume ratio of the mixed powder I to the anhydrous ethanol solution of salicylic acid is 1 g:3.5 mL;
[0055] The volume ratio of the anhydrous ethanol solution of salicylic acid, the anhydrous methanol solution of sodium borohydride, and the anhydrous ethanol solution of methyl iodide, sodium hydroxide, and sodium iodide is 1:1:2.5.
[0056] Preparation Example 3
[0057] The preparation of modified Raney nickel catalyst comprises the following steps:
[0058] (1) high-purity nickel and aluminum are smelted in a furnace at a mass ratio of 1:0.9, and after they are completely melted, lanthanum chloride is added at 10% of the total mass of the nickel and aluminum and the smelting is continued. After quenching and cooling, the mixture is added to a ball mill at 400 rpm to obtain alloy powder for later use;
[0059] (2) The chitosan nanofibers and alloy powder were placed in a bead mill at a weight ratio of 1:4 for grinding. After grinding at 3000 rpm for 16 min, they were placed in a corona machine for corona treatment at a voltage of 10 kV / m 2 , after corona treatment for 12 minutes, the mixed powder Ⅰ is prepared for use;
[0060] (3) The mixed powder I is ultrasonically dispersed in a sodium hydroxide solution and stirred at 80°C and 500 rpm for 6 h. Then, an anhydrous ethanol solution of salicylic acid is added, and the mixture is stirred and refluxed at 80°C and 500 rpm for 6 h. The mixture is filtered, washed with anhydrous ethanol for 5 times, dried in a vacuum drying oven at 50°C to constant weight, and then an anhydrous methanol solution of sodium borohydride is added. After sufficient reaction, the mixture is filtered, washed with deionized water for 5 times, dried in a vacuum drying oven at 50°C to constant weight, and then an anhydrous ethanol solution of iodomethane, sodium hydroxide, and sodium iodide is added. The mixture is reacted at 70°C for 12 h, filtered, washed with anhydrous ethanol for 3 times, washed with deionized water for 6 times, and finally dried in a vacuum drying oven at 50°C to constant weight to obtain a mixed powder II.
[0061] (4) The mixed powder II obtained in step (3) is placed in a DBD cold plasma device at 3 kW, and after being treated 9 times, it is taken out to obtain a modified Raney nickel catalyst III.
[0062] The weight volume ratio of the mixed powder I described in step (3) to the sodium hydroxide solution is 1 g:5 mL;
[0063] The weight-to-volume ratio of the mixed powder I to the anhydrous ethanol solution of salicylic acid is 1 g:4 mL;
[0064] The volume ratio of the anhydrous ethanol solution of salicylic acid, the anhydrous methanol solution of sodium borohydride, and the anhydrous ethanol solution of methyl iodide, sodium hydroxide, and sodium iodide is 1:1:3.
[0065] Example 1
[0066] A method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline comprises the following steps:
[0067] S1, methanol, 5-fluoro-2-nitroanisole, and modified Raney nickel catalyst are added to a hydrogenation kettle in sequence, hydrogen is introduced and the air is replaced three times, and the reaction is carried out under normal temperature and pressure conditions with stirring. After the reaction is completed, the modified Raney nickel catalyst is filtered out, and then rinsed with methanol, the filtrate is collected and concentrated to obtain 4-fluoro-2-methoxy-5-nitroaniline intermediate I;
[0068] S2. Add sulfuric acid (98%) to the reaction kettle, cool to 10-20°C, add 4-fluoro-2-methoxy-5-nitroaniline intermediate I dropwise while stirring, after the addition is completed, continue stirring for 1-2 hours, cool the reaction system to 6°C, then add potassium nitrate-cerium nitrate mixture in batches while performing gradient cooling, react in an ice bath at 0°C for 3-4 hours, adjust the system pH to 9-10 with liquid alkali, centrifuge and filter, wash the filter cake with water to obtain 4-fluoro-2-methoxy-5-nitroaniline wet product I filter cake, return the filter cake to the kettle, add water to pulp at room temperature, centrifuge, continue to wash the filter cake with water to obtain 4-fluoro-2-methoxy-5-nitroaniline wet product II filter cake, return the filter cake to the kettle, add ethanol to heat and dissolve, cool to -5-5°C, keep warm for crystallization, centrifuge, rinse with ethanol, and dry in vacuo to obtain 4-fluoro-2-methoxy-5-nitroaniline.
[0069] The weight ratio of 5-fluoro-2-nitroanisole to the modified Raney nickel catalyst in step S1 is 10 to 20:1;
[0070] The weight volume ratio of the 5-fluoro-2-nitroanisole and methanol is 1 g:8-10 mL.
[0071] The weight ratio of 4-fluoro-2-methoxy-5-nitroaniline intermediate I to potassium nitrate in step S2 is 1:0.7-0.8;
[0072] The weight-to-volume ratio of the 4-fluoro-2-methoxy-5-nitroaniline intermediate I and concentrated sulfuric acid is 1 g:1-2 mL.
[0073] The specific operation of adding the potassium nitrate-cerium nitrate mixture in batches while the gradient cooling described in step S2 is: adding the potassium nitrate-cerium nitrate mixture once every 6 to 8 minutes, maintaining the system temperature at 8 to 10° C. when the potassium nitrate-cerium nitrate mixture is added for the first time, and reducing the system temperature by 1 to 2° C. each time the potassium nitrate-cerium nitrate mixture is added, until it drops to 0° C., and the potassium nitrate-cerium nitrate mixture added each time is equal.
[0074] The potassium nitrate-cerium nitrate mixture is prepared by adding potassium nitrate and cerium nitrate into deionized water at a mass ratio of 1:0.1-0.16, dissolving them, mixing them, and then drying them.
[0075] Example 2
[0076] A method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline comprises the following steps:
[0077] S1, methanol, 5-fluoro-2-nitroanisole, and modified Raney nickel catalyst are added to a hydrogenation kettle in sequence, hydrogen is introduced and the air is replaced three times, and the reaction is carried out under normal temperature and pressure conditions with stirring. After the reaction is completed, the modified Raney nickel catalyst is filtered out, and then rinsed with methanol, the filtrate is collected and concentrated to obtain 4-fluoro-2-methoxy-5-nitroaniline intermediate I;
[0078] S2. Add sulfuric acid (98%) to the reaction kettle, cool to 10-20°C, add 4-fluoro-2-methoxy-5-nitroaniline intermediate I dropwise while stirring, after the addition is completed, continue stirring for 1-2 hours, cool the reaction system to 6°C, then add potassium nitrate-cerium nitrate mixture in batches while performing gradient cooling, react in an ice bath at 0°C for 3-4 hours, adjust the system pH to 9-10 with liquid alkali, centrifuge and filter, wash the filter cake with water to obtain 4-fluoro-2-methoxy-5-nitroaniline wet product I filter cake, return the filter cake to the kettle, add water to pulp at room temperature, centrifuge, continue to wash the filter cake with water to obtain 4-fluoro-2-methoxy-5-nitroaniline wet product II filter cake, return the filter cake to the kettle, add ethanol to heat and dissolve, cool to -5-5°C, keep warm for crystallization, centrifuge, rinse with ethanol, and dry in vacuo to obtain 4-fluoro-2-methoxy-5-nitroaniline.
[0079] The weight ratio of 5-fluoro-2-nitroanisole to the modified Raney nickel catalyst in step S1 is 10 to 20:1;
[0080] The weight volume ratio of the 5-fluoro-2-nitroanisole and methanol is 1 g:8-10 mL.
[0081] The weight ratio of 4-fluoro-2-methoxy-5-nitroaniline intermediate I to potassium nitrate in step S2 is 1:0.7-0.8;
[0082] The weight-to-volume ratio of the 4-fluoro-2-methoxy-5-nitroaniline intermediate I and concentrated sulfuric acid is 1 g:1-2 mL.
[0083] The specific operation of adding the potassium nitrate-cerium nitrate mixture in batches while the gradient cooling described in step S2 is: adding the potassium nitrate-cerium nitrate mixture once every 6 to 8 minutes, maintaining the system temperature at 8 to 10° C. when the potassium nitrate-cerium nitrate mixture is added for the first time, and reducing the system temperature by 1 to 2° C. each time the potassium nitrate-cerium nitrate mixture is added, until it drops to 0° C., and the potassium nitrate-cerium nitrate mixture added each time is equal.
[0084] The potassium nitrate-cerium nitrate mixture is prepared by adding potassium nitrate and cerium nitrate into deionized water at a mass ratio of 1:0.1-0.16, dissolving them, mixing them, and then drying them.
[0085] Example 3
[0086] A method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline comprises the following steps:
[0087] S1, methanol, 5-fluoro-2-nitroanisole, and modified Raney nickel catalyst are added to a hydrogenation kettle in sequence, hydrogen is introduced and the air is replaced three times, and the reaction is carried out under normal temperature and pressure conditions with stirring. After the reaction is completed, the modified Raney nickel catalyst is filtered out, and then rinsed with methanol, the filtrate is collected and concentrated to obtain 4-fluoro-2-methoxy-5-nitroaniline intermediate I;
[0088] S2. Add sulfuric acid (98%) to the reaction kettle, cool to 10-20°C, add 4-fluoro-2-methoxy-5-nitroaniline intermediate I dropwise while stirring, after the addition is completed, continue stirring for 1-2 hours, cool the reaction system to 6°C, then add potassium nitrate-cerium nitrate mixture in batches while performing gradient cooling, react in an ice bath at 0°C for 3-4 hours, adjust the system pH to 9-10 with liquid alkali, centrifuge and filter, wash the filter cake with water to obtain 4-fluoro-2-methoxy-5-nitroaniline wet product I filter cake, return the filter cake to the kettle, add water to pulp at room temperature, centrifuge, continue to wash the filter cake with water to obtain 4-fluoro-2-methoxy-5-nitroaniline wet product II filter cake, return the filter cake to the kettle, add ethanol to heat and dissolve, cool to -5-5°C, keep warm for crystallization, centrifuge, rinse with ethanol, and dry in vacuo to obtain 4-fluoro-2-methoxy-5-nitroaniline.
[0089] The weight ratio of 5-fluoro-2-nitroanisole to the modified Raney nickel catalyst in step S1 is 10 to 20:1;
[0090] The weight volume ratio of the 5-fluoro-2-nitroanisole and methanol is 1 g:8-10 mL.
[0091] The weight ratio of 4-fluoro-2-methoxy-5-nitroaniline intermediate I to potassium nitrate in step S2 is 1:0.7-0.8;
[0092] The weight-to-volume ratio of the 4-fluoro-2-methoxy-5-nitroaniline intermediate I and concentrated sulfuric acid is 1 g:1-2 mL.
[0093] The specific operation of adding the potassium nitrate-cerium nitrate mixture in batches while the gradient cooling described in step S2 is: adding the potassium nitrate-cerium nitrate mixture once every 6 to 8 minutes, maintaining the system temperature at 8 to 10° C. when the potassium nitrate-cerium nitrate mixture is added for the first time, and reducing the system temperature by 1 to 2° C. each time the potassium nitrate-cerium nitrate mixture is added, until it drops to 0° C., and the potassium nitrate-cerium nitrate mixture added each time is equal.
[0094] The potassium nitrate-cerium nitrate mixture is prepared by adding potassium nitrate and cerium nitrate into deionized water at a mass ratio of 1:0.1-0.16, dissolving them, mixing them, and then drying them.
[0095] Comparative Example 1
[0096] On the basis of Example 2, the modified Raney nickel catalyst was replaced with a commercially available Raney nickel catalyst, and the rest of the technical scheme was consistent with that of Example 2.
[0097] Comparative Example 2
[0098] On the basis of Example 2, the modified Raney nickel catalyst was replaced with a 5% palladium-carbon catalyst, and the rest of the technical scheme was consistent with that of Example 2.
[0099] Comparative Example 3
[0100] On the basis of Example 2, the addition of the potassium nitrate-cerium nitrate mixture in batches while performing gradient cooling is replaced by adding the potassium nitrate-cerium nitrate mixture in batches at 0°C, and the rest of the technical scheme is consistent with the technical scheme of Example 2.
[0101] Comparative Example 4
[0102] On the basis of Example 2, the potassium nitrate-cerium nitrate mixture in step S2 is replaced with potassium nitrate, and the rest of the technical scheme is consistent with the technical scheme of Example 2.
[0103] The yield of each embodiment and comparative example was calculated and statistically analyzed, and the purity was determined by HPLC. The statistical results are shown in Table 1 below:
[0104] Table 1
[0105] Yield (%) purity(%) Example 1 97.3 ≥99% Example 2 98.2 ≥99% Example 3 97.8 ≥99% Comparative Example 1 94.6 93.2 Comparative Example 2 95.1 95.1 Comparative Example 3 96.2 94.9 Comparative Example 4 96.5 97.1
[0106] It can be seen from Table 1 above that the synthesis method of 4-fluoro-2-methoxy-5-nitroaniline of the present invention can effectively improve the purity and yield of the product.
[0107] The present invention also conducted a recycling test on the modified Raney nickel catalyst of Preparation Example 2, and the reaction system used was the reaction system of Example 2. After the reaction was completed, the catalyst in the reaction system was filtered and recovered, and after being washed with methanol, it was directly put into the next reaction system for reaction without any other treatment. The test results are shown in Table 2 below:
[0108] Table 2
[0109]
[0110]
[0111] It can be concluded from Table 2 above that in the reaction system of the present invention, the catalyst of the present invention has excellent reaction effect. After more than 7 catalyst cycles, the yield and selectivity of the product are almost unchanged, which shows that the modified Raney nickel catalyst prepared by the method of the present invention has good catalyst stability and can maintain its activity and selectivity for a long time, thereby extending the service life of the catalyst.
[0112] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline, characterized in that: The steps include: S1, methanol, 5-fluoro-2-nitroanisole, and modified Raney nickel catalyst are added to a hydrogenation kettle in sequence, hydrogen is introduced and the air is replaced three times, and the reaction is carried out under normal temperature and pressure conditions with stirring. After the reaction is completed, the modified Raney nickel catalyst is filtered out, and then rinsed with methanol, the filtrate is collected and concentrated to obtain 4-fluoro-2-methoxy-5-nitroaniline intermediate I; S2. Add sulfuric acid to the reaction kettle, cool to 10-20°C, add 4-fluoro-2-methoxy-5-nitroaniline intermediate I dropwise while stirring, after the addition is completed, continue stirring for 1-2 hours, cool the reaction system to 6°C, then add potassium nitrate-cerium nitrate mixture in batches while performing gradient cooling, react in an ice bath at 0°C for 3-4 hours, adjust the system pH to 9-10 with liquid alkali, centrifuge and filter, wash the filter cake with water to obtain 4-fluoro-2-methoxy-5-nitroaniline wet product I filter cake, return the filter cake to the kettle, add water to pulp at room temperature, centrifuge, continue to wash the filter cake with water to obtain 4-fluoro-2-methoxy-5-nitroaniline wet product II filter cake, return the filter cake to the kettle, add ethanol to heat and dissolve, cool to -5-5°C, keep warm for crystallization, centrifuge, rinse with ethanol, and vacuum dry to obtain 4-fluoro-2-methoxy-5-nitroaniline.
2. A method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline according to claim 1, characterized in that: The preparation of the modified Raney nickel catalyst comprises the following steps: (1) high-purity nickel and aluminum are smelted in a furnace, and after they are completely melted, lanthanum chloride is added to continue smelting, and after quenching and cooling, they are added to a ball mill for ball milling to obtain alloy powder for use; (2) grinding the chitosan nanofibers and the alloy powder in a bead mill at a weight ratio of 1:1 to 4, grinding at 2000 to 3000 rpm for 10 to 16 minutes, and then placing the mixture in a corona machine for corona treatment. After the grinding, a mixed powder I is obtained for use. (3) Ultrasonic dispersion of the mixed powder I in a sodium hydroxide solution, stirring at 60-80° C. and 300-500 rpm for 4-6 h, adding an anhydrous ethanol solution of salicylic acid, stirring and refluxing at 60-80° C. and 300-500 rpm for 4-6 h, filtering, washing with anhydrous ethanol 3-5 times, drying in a vacuum drying oven at 40-50° C. to constant weight, adding an anhydrous methanol solution of sodium borohydride, filtering after sufficient reaction, washing with deionized water 3-5 times, drying in a vacuum drying oven at 40-50° C. to constant weight, adding an anhydrous ethanol solution of iodomethane, sodium hydroxide and sodium iodide, reacting at 60-70° C. for 10-12 h, filtering, washing with anhydrous ethanol 2-3 times, washing with deionized water 3-6 times, and finally drying in a vacuum drying oven at 40-50° C. to constant weight to obtain a mixed powder II; (4) The mixed powder II obtained in step (3) is placed in a DBD cold plasma device for cold plasma treatment and taken out after completion.
3. A method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline according to claim 2, characterized in that: The mass ratio of nickel to aluminum in step (1) is 1:0.7-0.9, and the mass of lanthanum chloride is 8-10% of the total mass of nickel and aluminum; The grinding speed of the ball mill is 300-400 rpm.
4. A method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline according to claim 2, characterized in that: The voltage of the corona treatment described in step (2) is 5 to 10 kV / m 2 The corona treatment time is 10 to 12 minutes.
5. The method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline according to claim 2, characterized in that: The weight volume ratio of the mixed powder I described in step (3) to the sodium hydroxide solution is 1 g: 4-5 mL; The weight-volume ratio of the mixed powder I to the anhydrous ethanol solution of salicylic acid is 1 g: 3-4 mL; The volume ratio of the anhydrous ethanol solution of salicylic acid, the anhydrous methanol solution of sodium borohydride and the anhydrous ethanol solution of methyl iodide, sodium hydroxide and sodium iodide is 1:1:2-3.
6. The method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline according to claim 2, characterized in that: The power of the cold plasma treatment in step (4) is 1 to 3 kW, and the number of treatments is 3 to 9 times.
7. The method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline according to claim 1, characterized in that: The weight ratio of 5-fluoro-2-nitroanisole to the modified Raney nickel catalyst in step S1 is 10 to 20:1; The weight volume ratio of the 5-fluoro-2-nitroanisole and methanol is 1 g:8-10 mL.
8. The method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline according to claim 1, characterized in that: The weight ratio of 4-fluoro-2-methoxy-5-nitroaniline intermediate I to potassium nitrate in step S2 is 1:0.7-0.8; The concentrated sulfuric acid is 98% sulfuric acid by mass; The weight-to-volume ratio of the 4-fluoro-2-methoxy-5-nitroaniline intermediate I and concentrated sulfuric acid is 1 g:1-2 mL.
9. The method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline according to claim 1, characterized in that: The specific operation of adding the potassium nitrate-cerium nitrate mixture in batches while the gradient cooling described in step S2 is: adding the potassium nitrate-cerium nitrate mixture once every 6 to 8 minutes, maintaining the system temperature at 8 to 10° C. when the potassium nitrate-cerium nitrate mixture is added for the first time, and reducing the system temperature by 1 to 2° C. each time the potassium nitrate-cerium nitrate mixture is added, until it drops to 0° C., and the potassium nitrate-cerium nitrate mixture added each time is equal.
10. A method for synthesizing 4-fluoro-2-methoxy-5-nitroaniline according to claim 9, characterized in that: The potassium nitrate-cerium nitrate mixture is prepared by adding potassium nitrate and cerium nitrate into deionized water at a mass ratio of 1:0.1-0.16, dissolving them, mixing them, and then drying them.